Beyond Incumbents and Entrants: An Empirical Exploration of Product Line Management Strategy after Radical Technological Change - JONES, Neil (Institutional Knowledge at Singapore Management University, 1999)
Research on firm performance after the introduction of a radical technological change has primarily concerned itself with differences between incumbents and entrants. This paper explores other factors that may influence firm performance over the longer term after a radical change -- specifically, those related to product line development strategy. Following a radical change, a period of incremental technological change typically creates the opportunity for rapid development of new products. In such settings, strategies to manage multiple products, including families of products that may be derived from a common platform, may be expected to impact competitive performance. The data for the study are from the telecommunications switching sector, specifically the private branch exchange (PBX) industry. 56 firms and over 240 new products were analyzed over 22 years. For the literature on competition after radical technological change, this study shows that incumbent-entrant based explanations of firm performance are incomplete. Specifically, the results demonstrate that various dimensions of product line strategy explain significant additional variation in firm performance.